Quality Indicators for Systematic Reviews in Behavioral Disorders. (February 2017) - Maggin, Daniel M.; Talbott, Elizabeth; Van Acker, Eryn Y.; Kumm, Skip
Special education researchers, practitioners, and policy makers continue to work toward developing and implementing empirically supported practices and policies to address the academic, social, and postschool challenges confronting students with emotional and behavioral disorders. The systematic review has become an essential vehicle for compiling and disseminating research findings on an array of topics. Given the importance and impact of these research summaries, it is instructive to take stock of the extent to which reviews in our field adhere to current standards. Drawing from a number of sources in the social and behavioral sciences, we propose and describe a series of quality indicators for systematic reviews. We applied these indicators to systematic reviews published in Behavioral Disorders between 2005 and 2016 with the broader goal of identifying areas of methodological strength and areas for improvement. Results indicate that the sample of systematic reviews demonstrated particular strength in several procedural domains such as the specification of inclusion criteria, identifying the electronic databases used for the search, and describing the plan for data analysis. We also identified a number of areas to which researchers might devote greater attention to increase the rigor of systematic reviews in the field. Findings are contextualized within the importance of research transparency and reporting to improve practice and policy.